2018
DOI: 10.21037/atm.2017.11.38
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life assessment in esophagectomy patients

Abstract: Esophagectomy is the mainstay of curative therapy for esophageal cancer; however, it is associated with significant morbidity and mortality, with subsequent major impact on quality of life. This paper reviews the evaluation of health-related quality of life (HRQOL) in esophageal cancer patients undergoing curative intent therapy, the relationship between postoperative HRQOL and survival as well the potential utility of pre-treatment HRQOL as a prognostic tool. HRQOL assessment is valuable in helping clinicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
0
23
0
2
Order By: Relevance
“…There are no biomarkers to predict the onset of these forms of endocrine disorders, so regular screening for early detection is mandatory ( 10 ). An in-depth screening for risk factors of autoimmune dysfunction, including personal or familial autoimmune illness like vitiligo, arthritis or autoimmune endocrinopathies may help in the rational selection of patients for this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There are no biomarkers to predict the onset of these forms of endocrine disorders, so regular screening for early detection is mandatory ( 10 ). An in-depth screening for risk factors of autoimmune dysfunction, including personal or familial autoimmune illness like vitiligo, arthritis or autoimmune endocrinopathies may help in the rational selection of patients for this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A avaliação da QVRS em pacientes com câncer de esôfago submetidos à terapia por esofagectomia tem o intuito de ajudar os médicos a entender o impacto da cirurgia e os vários tratamentos e pode ser um complemento importante na tomada de decisão compartilhada, orientação e planejamento do tratamento (ALGHAMEDI et al, 2018).…”
Section: Resultsunclassified
“…Um estudo relatou que pacientes com câncer de esôfago e que também eram acometidos por comorbidades, como por exemplo, distúrbios cardiovasculares, renais, respiratórios, hepáticos, bem como por diabetes, apresentam pior qualidade de vida relacionada à saúde, durante o pós-operatório da esofagectomia (ALGHAMEDI et al, 2018).…”
Section: Resultsunclassified
“…Esophagectomy for cancer strongly impairs postoperative health-related quality of life (HRQL) [1,2]. A systematic review showed that patients undergoing esophagectomy for cancer had scores of physical function, vitality, and performance of health in general significantly lower than those obtained from the reference population [3].…”
Section: Introductionmentioning
confidence: 99%